Effect of Subjective Well-being and Quality of Work Life on Job Commitment of Hospital Staff - A. Mansourlakouraj; D. Abdollahi; I. Rasouli (Afarand Scholarly Publishing Institute, 2019)
Aims: Job commitment is one of the characteristics of a positive relationship between an organization and its employees that makes it effective and conducive the performance of the organization. Regarding the importance of this issue, the present study was conducted with the aim of investigating the effect of subjective well-being and quality of work life on job commitment of staff of Isar Hospital, Ardabil. Instrument & Methods: In the present descriptive correlational study conducted in 2018, all the staff of Isar Hospital were selected and examined. The instruments, including Blavo Career Commitment Scale, standard questionnaire of quality of work life of Walton, and subjective well-being scale of Keyes and Magyar-Moe were used to collect the required information. The data were analyzed by SPSS 23 software, using Pearson correlation coefficient and multivariate regression analysis. Findings: There was a positive and significant correlation between subjective well-being (p<0.01; r=0.78) and quality of work life (p<0.01; r=0.42). Subjective well-being alone expressed 60.8% of the variance in job commitment of hospital staff and by adding quality of work life, the value reached 62.0% (p<0.01). Conclusion: The high subjective well-being and quality of work life increase job commitment in hospital staff.